Challenging the injustice of poverty : agendas for inclusive development in South Asia - Sobhan, Rehman (SAGE, 2010)
This book explores issues related to poverty in South Asia in a two-pronged mannerby focusing on injustice created and perpetuated by the unjust nature of a social order as its source and by providing concrete suggestions about how policymakers may move to challenge these injustices. Drawing on research inputs from studies across various South Asian countries, the book redefines poverty as a process that excludes certain segments of society from equitable participation in development opportunities as well as decision making. It further identifies a variety of operational ideas which can be us.